Macrophage responses to lipopolysaccharide are modulated by a feedback loop involving prostaglandin E2, dual specificity phosphatase 1 and tristetraprolin - Tina Tang (Nature Portfolio, 2017)
Abstract In many different cell types, pro-inflammatory agonists induce the expression of cyclooxygenase 2 (COX-2), an enzyme that catalyzes rate-limiting steps in the conversion of arachidonic acid to a variety of lipid signaling molecules, including prostaglandin E2 (PGE2). PGE2 has key roles in many early inflammatory events, such as the changes of vascular function that promote or facilitate leukocyte recruitment to sites of inflammation. Depending on context, it also exerts many important anti-inflammatory effects, for example increasing the expression of the anti-inflammatory cytokine interleukin 10 (IL-10), and decreasing that of the pro-inflammatory cytokine tumor necrosis factor (TNF). The tight control of both biosynthesis of, and cellular responses to, PGE2 are critical for the precise orchestration of the initiation and resolution of inflammatory responses. Here we describe evidence of a negative feedback loop, in which PGE2 augments the expression of dual specificity phosphatase 1, impairs the activity of mitogen-activated protein kinase p38, increases the activity of the mRNA-destabilizing factor tristetraprolin, and thereby inhibits the expression of COX-2. The same feedback mechanism contributes to PGE2-mediated suppression of TNF release. Engagement of the DUSP1-TTP regulatory axis by PGE2 is likely to contribute to the switch between initiation and resolution phases of inflammation.